2007
DOI: 10.1111/j.1365-2443.2007.01134.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that SV40 VP1–DNA interactions contribute to the assembly of 40‐nm spherical viral particles

Abstract: The simian virus 40 (SV40) particle is mainly composed of the major capsid protein termed VP1. VP1 self-assembles into virus-like particles (VLPs) of approximately 40 nm in diameter when over-expressed in bacteria or in insect cells, but purified VP1 does not form such a structure under physiological conditions, and thus, the mechanism of VP1 assembly is not well understood. Using a highly purified VP1 assembly/disassembly system in vitro , here we provide evidence that DNA is a factor that contributes to VP1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…Packaging different nucleic acid lengths can affect the size of the VLP. For example, Tsukamoto et al (2007) showed that packaging lower molecular weight linear DNA in VLPs caused significant decreases in size. Similarly, studies of the packaging of RNA strands of varied length (Thomas et al, 2004) of the cowpea mosaic virus with ES-DMA found that encapsulation of longer RNA strands increased the average diameter of the virus by approximately 1 nm.…”
Section: Packaging Of Non-viral Nucleic Acidmentioning
confidence: 98%
“…Packaging different nucleic acid lengths can affect the size of the VLP. For example, Tsukamoto et al (2007) showed that packaging lower molecular weight linear DNA in VLPs caused significant decreases in size. Similarly, studies of the packaging of RNA strands of varied length (Thomas et al, 2004) of the cowpea mosaic virus with ES-DMA found that encapsulation of longer RNA strands increased the average diameter of the virus by approximately 1 nm.…”
Section: Packaging Of Non-viral Nucleic Acidmentioning
confidence: 98%
“…In the dissociation buffer, the disulfide bonds are broken by β-mercaptoethanol, and the Ca 2+ that stabilizes the VNP structures is chelated by ethylenediaminetetraacetic acid. 27,32 The low ionic strength and the lack of disulfide bonds lead to the collapse of the VNPs. This means that the concentrations of salt and Ca 2+ significantly contribute to the formation of VNPs.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28] However, in this study, it was discovered that VP1 can be assembled into capsids when there are QDs in the dissociation buffer and that the QDs are encapsulated in the SV40 capsids. Analysis of the transmission electron microscopy (TEM), dynamic light scattering (DLS), sucrose density gradient centrifugation (SDGC), and cryo-electron microscopy (cryo-EM) single particle reconstruction data verified this result.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations